The Spatial Development of India - Desmet, Klaus (World Bank, Washington, DC, 2012)
In the last two decades the Indian economy has been growing unabatedly, with memories of the Hindu rate of growth rapidly fading. But this unprecedented growth has also resulted in widening spatial disparities. While cities such as Hyderabad have emerged as major clusters of high development, many rural areas have been left behind with little development benefits accruing to them. India's mega-cities have continued to grow. This situation raises a number of important policy questions. Should India aim to spread development more equally across space? Are India's cities becoming too large? Should the government invest in infrastructure in the large cities to reduce congestion or in medium-sized locations to facilitate the emergence of new economic clusters? What are the tradeoffs between agglomeration economies and congestion costs? How different is India s experience compared with China and USA?